The Women’s Law (tou gynaikeiou nomos) in the Kallipolis of Plato’s Republic - Cornelli, Gabriele (2022)
The Women’s Law discussed in book V of the Republic, known as the first wave, is a notorious example of Socrates’ reformist intention to achieve justice in the polis. The legislation for women, in general, has historically been relegated by the Republic interpreters. This paper aims to analyze this passage, from 449a to 457c, through the arguments provided by Socrates seen as crucial to conceive equality between the sexes (under the ontological foundation of the same human nature) as well as to favor institutional change according to nature, kata physin, thus opening the possibility for women to govern the polis. Before leaving for the external confrontation, Socrates considers it urgent that his interlocutors, Adeimantus, Glaucon, and Polemarchus, agree with each other. Thus, he urges them to start the argument by questioning the human nature of women and their capacity for the same functions (erga) performed by men in the city. The examination of the intelligible enabled the logos on women’s intellectual capacity to support adequate legislation. Such nomos put into practice proves to be the best for the city and its guardians. To that extent, Socrates can conclude the investigation with a consensus on what to do and willingness to confront opposing opinions in the city urgently.